Genome-wide association study identifies four SNPs associated with response to platinum-based neoadjuvant chemotherapy for cervical cancer - Li, Xiong; Huang, Kecheng; Zhang, Qinghua; Zhou, Jin; Sun, Haiying; Tang, Fangxu; Zhou, Hang; Hu, Ting; Wang, Shaoshuai; Jia, Yao; Yang, Ru; Chen, Yile; et al. (Scientific reports, 2017)
To identify genomic markers associated with the response to neoadjuvant chemotherapy (NACT) in patients with cervical cancer, we performed a three-stage genome-wide association study (GWAS) in the Han Chinese population. A total of 596 patients with stage IA2-IIIB cervical cancer were enrolled in this study. One single nucleotide polymorphism (SNP) (rs6812281, per allele OR = 2.37, P = 9.0 × 10 −9 ) located at 4q34.3 reached GWAS significance ( P < 5.0 × 10 −8 ). Another three SNPs, rs4590782 (10q26.2, P = 1.59 × 10 −5 , per allele OR = 0.48), rs1742101 (14q32.11, P = 7.11 × 10 −6 , per allele OR = 0.52), and rs1364121 (16q23.3, P = 3.15 × 10 −6 , per allele OR = 1.98), exhibited strong evidence of associations with response to neoadjuvant chemotherapy. Patients with a C allele (CT + CC) of rs4590782 had better 5-year overall survival rates (82.9% vs. 75.8%, P = 0.083) and 5-year disease-free survival rate (80.8% vs. 72.7%, P = 0.021) than those without a C allele. Our findings help to characterize the genetic etiology of the response to neoadjuvant chemotherapy in patients with cervical cancer.